Brain, Nerves, and Senses - Parker, Steve (Milwaukee, WI Gareth Stevens, 2005)
The brain contains a massive database and monitoring system fully equipped with the ultimate search engine. Discover how your five senses supply constant input to your master control center about everything in your external and internal environment, and how your nerves respond.
5 - 9
Keywords: Nervous system